Pneumonia by Aelurostrongylus abstrusus in a Leopardus tigrinus: Case study - Rincón-Alarcón, Diego F; Doncel, Benjamín; Cortés-Vecino, Jesús A (Revista Colombiana de Ciencias Pecuarias, 2024)
Anamnesis: A polytraumatized wild oncilla (Leopardus tigrinus) was admitted to the Unidad de Rehabilitación y Rescate de Animales Silvestres (URRAS) veterinary clinic of the Universidad Nacional de Colombia. Despite the medical efforts, the animal died six hours later. Clinical and laboratory findings: Necropsy examination revealed multiple white nodules of about 2 mm in diameter distributed on the visceral surface of lung caudal lobes. Histopathology revealed lymphoplasmacytic interstitial pneumonia with multiple coiled larvae of metastrongyloid nematodes in alveoli and bronchioles. First-stage Aelurostrongylus abstrusus nematode was identified in a fecal sample using the Ritchie copromicroscopic technique. Conclusion: This study reports an incidental severe pulmonary parasitism caused by A. abstrusus in a wild Oncilla (L. tigrinus). This is the first report of A. abstrusus infection associated with pathological lesions in a L. tigrinus from Colombia.